2005
DOI: 10.1164/rccm.200411-1444oc
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Treatment of Community-acquired Pneumonia

Abstract: Adherence to guidelines mainly depends on the hospital and the specialty and training status of prescribing physicians. Nonadherence was higher in nonpneumology specialists, and is an independent risk factor for treatment failure and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
91
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 39 publications
10
91
1
10
Order By: Relevance
“…However, that proportion was lower than were those reported in other studies involving ward and ICU patients (79.6%-84.0%). (6,17) Previous studies have reported that guideline-concordant antibiotic therapy is associated with lower short-term mortality rates. (7,16,17) A study conducted in Brazil showed a trend toward a reduction in the overall mortality rate after the implementation of CAP guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, that proportion was lower than were those reported in other studies involving ward and ICU patients (79.6%-84.0%). (6,17) Previous studies have reported that guideline-concordant antibiotic therapy is associated with lower short-term mortality rates. (7,16,17) A study conducted in Brazil showed a trend toward a reduction in the overall mortality rate after the implementation of CAP guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Although there is no consensus in the literature, various studies have shown that the systematic use of CAP guidelines results in an increase in the proportion of patients treated as outpatients (with no worsening of outcomes), as well as in a reduction in 30-day mortality, in-hospital mortality, length of hospital stay, time to clinical stability, and complications in those treated as inpatients. (5)(6)(7)(8)(9) The primary objective of the present study was to evaluate the agreement between the criteria used for hospitalization of CAP patients in the Hospital das Clínicas da Universidade Federal de Minas Gerais (HC/UFMG, Federal University of Minas Gerais Hospital das Clínicas), located in the city of Belo Horizonte, Brazil, in the 2005-2007 period and those of the Brazilian Thoracic Association guidelines, as well as to evaluate the association of that agreement with 30-day mortality. The secondary objective of the study was to evaluate the association between the agreement of the treatment given with that recommended in the Brazilian guidelines for CAP and length of hospital stay, microbiological profile, 12-month mortality, incidence of complications, need for ICU admission, need for mechanical ventilation, and variables associated with 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto a los pacientes ingresados la tasa de mortalidad global es similar a la descrita en la literatura, entre el 5 y 13% (1,(5)(6)(7)(8)13,24). El porcentaje de fracasos de tratamiento es también comparable a la de otros trabajos realizados en nuestro medio, 15% en el trabajo de Menéndez (20).…”
Section: Discussionunclassified
“…Previous studies have shown that clinical judgment plays an important role in decisionmaking because severity of illness scores do not capture all important clinical risk factors to determine that most appropriate site for treatment (11). However, previous studies (12,13,16,21) are limited by several factors: (I) retrospective design; (II) small sample size; (III) different severity of illness scores; (IV) influence of physician preferences; (V) local hospital practices; and (VI) active participation in an intervention trial (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%